Hard rock landforms generate 130 km ice shelf channels through water focusing in basal corrugations. Issue 1 (December 2018) - Jeofry, Hafeez; Ross, Neil; Le Brocq, Anne; Graham, Alastair G.C.; Li, Jilu; Gogineni, Prasad; Morlighem, Mathieu; Jordan, Thomas; Siegert, Martin
Abstract Satellite imagery reveals flowstripes on Foundation Ice Stream parallel to ice flow, and meandering features on the ice-shelf that cross-cut ice flow and are thought to be formed by water exiting a well-organised subglacial system. Here, ice-penetrating radar data show flow-parallel hard-bed landforms beneath the grounded ice, and channels incised upwards into the ice shelf beneath meandering surface channels. As the ice transitions to flotation, the ice shelf incorporates a corrugation resulting from the landforms. Radar reveals the presence of subglacial water alongside the landforms, indicating a well-organised drainage system in which water exits the ice sheet as a point source, mixes with cavity water and incises upwards into a corrugation peak, accentuating the corrugation downstream. Hard-bedded landforms influence both subglacial hydrology and ice-shelf structure and, as they are known to be widespread on formerly glaciated terrain, their influence on the ice-sheet-shelf transition could be more widespread than thought previously. Subglacial landforms, formed by glacial processes operating over long timescales, influence ice dynamics. Here, the authors show how mega-scale landforms at an Antarctic ice stream grounding zone modulate basal water flow, causing extensive channels in the ice shelf downstream that may impact its structure.